Health-Related Quality of Life Improves in Parallel with FEV1 and 6-Minute Walking Distance Test at Between 3 and 12 Months in Critical COVID-19 Survivors - Stephanie André; Anne-Violette Bruyneel; Audrey Chirumberro; Alain Roman; Marc Claus; Stephane Alard; Nathalie De Vos; Marie Bruyneel (American Journal of Medicine Open, 2023)
Background: In COVID-19 intensive care unit (ICU)–admitted patients, multiorgan acute complications lead to long-lasting sequelae. The aim of this study was to assess (1) changes in chest CT, pulmonary function test (PFT), functional capacity (6-minute walking distance test (6MWT)), and health-related quality of life (HR-QoL) among ICU COVID-19 survivors at 3, 6, and 12 months after ICU discharge and (2) predictors of persistent impairment/improvement in 6MWT and HR-QoL. Methods: ICU COVID-19 survivors were prospectively included. Outcomes at 3, 6, and 12 months included PFT, 6MWT, respiratory muscle strength (RMS), HR-QoL (SF-36), Medical Research Council dyspnea scale (mMRC), and post-COVID Functional Status scale. Results: Eighty-seven survivors were included, from June 3, 2020, to September 2, 2021. At 12 months, 50% of PFT were normal, 46% were restrictive, and 22% showed reduced diffusing capacity for carbon monoxide (DLCO). Impaired DLCO was associated with ICU length of stay and age. In mixed linear model analysis, improvements in RMS and mMRC persisted over time regardless of the adjustments applied (P ≤ .050). SF-36 improved in parallel with FEV1 and 6MWT between 3 and 12 months (P ≤ .044), while increment in DLCO correlated with changes in FEV1 and total lung capacity (TLC) (p ≤ 0.026). Conclusions: This longitudinal study demonstrated that improvements in SF-36 occur in parallel with improvements in FEV1 and 6MWT between 3 and 12 months post-ICU discharge in a sample of critically ill COVID-19 patients. However, PFT remained, however, abnormal in 50% of patients. Based on continued improvements observed from 3 to 12 months, it is anticipated that COVID-19 ICU patients will continue to recover similarly to ARDS patients.